DOES IT MATTER WHEN YOU REVIEW?: INPUT SPACING, ECOLOGICAL VALIDITY, AND THE LEARNING OF L2 VOCABULARY. Issue 5 (9th December 2021) - Rogers, John; Cheung, Anisa
Abstract: This study is a conceptual replication of Rogers and Cheung's (2018) investigation into distribution of practice effects on the learning of L2 vocabulary in child EFL classrooms in Hong Kong. Following a pretest, treatment, delayed posttest design, 66 primary school students (Cantonese L1) studied 20 vocabulary items over three training episodes under spaced-short (1-day interval) or spaced-long (8-day interval) learning conditions. The spacing of the vocabulary items was manipulated within-participants, and learning was assessed using crossword puzzles following a 4-week delay. While Rogers and Cheung (2018) resulted in minimal overall learning with a slight advantage for the spaced-short group, this study found large learning gains across the experimental conditions with no significant differences between the two learning schedules. Taken together, these results provide evidence that the results from previous research examining input spacing with adult populations in laboratory contexts might not generalize to authentic child learning contexts.